Endometrial flushing αVβ3 integrin, glycodelin and PGF2α levels for evaluating endometrial receptivity in women with polycystic ovary syndrome, myoma uteri and endometrioma. (2nd September 2017) - Demir, Mustafa; Ince, Onur; Ozkan, Bulent; Kelekci, Sefa; Sutcu, Recep; Yilmaz, Bulent
Abstract: The aim of this cross-sectional study is to compare endometrial flushing fluid levels of αV β3 integrin, glycodelin and PGF2α during the midluteal phase of the menstrual cycle of women with polycystic ovary syndrome (PCOS, n = 20), myoma uteri ( n = 20) and endometrioma ( n = 19) with the healthy controls ( n = 20). After collecting samples at the midluteal phase of ovulatory volunteers and storing them at −80 °C, αV β3 integrin, glycodelin and PGF2α levels were analyzed using ELISA. The mean ages of the groups were 28.90 ± 5.45, 37.25 ± 2.73, 32.84 ± 6.62 and 32.15 ± 5.18 in PCOS, myoma uteri, endometrioma and control groups, respectively. The αV β3 integrin level (ng/ml) was statistically significantly higher in endometrioma group (9.70 ± 1.72, p < 0.05) as compared to myoma uteri and control groups. Similarly, glycodelin level (ng/ml) was significantly higher in endometrioma group (341.04 ± 93.32) than PCOS ( p < 0.01), myoma uteri ( p < 0.001) and healthy subjects ( p < 0.001). Moreover, PGF2α level (350.04 ± 464.50 ng/ml) was significantly higher in PCOS group relative to myoma uteri ( p < 0.001), endometrioma ( p < 0.05) and control ( p < 0.05) groups. In conclusion, αV β3 integrin level was significantly higher in endometrioma subjects than those with myoma uteri and control groups; glycodelin level was significantly higher in endometrioma group than other three groups, and lastly, PCOS patients had significantly higher PGF2α levels than those patients with myoma uteri, endometrioma and controls.